The Evolution of the Islamic Architectural Dome Feature - Lasindu, Gamage; Shukri, Sharyzee Mohmad; Taib, Idris (MAJ - Malaysia Architectural Journal, 2023)
The paper intends to provide a discussion on the changes and developments observed in the dome as an architectural feature in Islamic architecture. The findings will be based on several past literature analyses on the historical evolution of the dome until the modern era. The development of the dome in the early centuries followed developments in materials, building technology, elements, shapes, and several other aspects. The dome of Masjid Raja Haji Fi Sabilillah is a suitable representation of a functional modern dome. This dome was designed beyond expectations with high functionality and its ability to contribute to a building that has achieved a platinum level in green building certification proves how this dome is a representation of the future of the field as well. The dome study was carried out through site visits, a semi-structured interview with the project director, and analyzing past publications, which in conclusion proved that the dome at the mosque is a unique representation of the new potential of dome architecture.